Methodology for Development of a Community Level Intervention Module for Physical Illness in Persons with Mental Illness (CLIPMI). Issue 6 (December 2020) - Govindan, Ramanujam; Rangaswamy, Thara; John, Sujit; Kandasamy, Sunitha
Background and Objectives: Medical illnesses seen in persons with psychiatric disorders are important but often ignored causes of increased morbidity and mortality. Hence, a community level intervention program addressing the issue is proposed. Materials and Methods: Patients with severe mental illnesses will be identified by a door-to-door survey and assessed for comorbid physical illnesses like anemia, hypertension, diabetes, and so on. They will then be randomized into two groups. The treatment as usual (TAU) group will not receive intervention from the trained community level workers, while the Intervention group will receive it. Results: The two groups will be compared for the prevalence and severity of comorbid physical illnesses. The expected outcome is compared to the TAU group, the intervention group will have a greater reduction in the morbidity due to physical illnesses and improved mental health. Conclusion: If successful, the module can be incorporated into the community level mental health delivery system of the District Mental Health Program (DMHP).